(untitled) (Journal of Partial Differential Equations, 2020)
Maximum principles for weak solutions of nonhomogeneous subelliptic p-Laplace equations related to smooth vector fields X_j satisfying the Hömander condition are proved by the choice of suitable test functions and the adaption of the classical Moser iteration method. Some applications are given in this paper.